Consumer Acceptability of Various Gluten-Free Scones with Rice, Buckwheat, Black Rice, Brown Rice, and Oat Flours - Jihyuk Chae; Sukyung Kim; Jeok Yeon; Sohui Shin; Seyoung Ju (Foods, 2025)
Due to consumer needs and the prevalence of gluten-related disorders such as celiac disease, the gluten-free food market is expanding rapidly and is expected to surpass USD 2.4 billion by 2036. The objective of this study was to substitute wheat flour with oat, black rice, brown rice, buckwheat, and rice flours in the production of gluten-free scones, to assess consumer acceptability, and to identify factors contributing to consumer acceptability using check-all-that-apply questions. The 10 attributes of appearance, color, texture, grainy flavor, sweetness, familiar flavor, novelty, familiarity, moistness, and consistency exhibited statistically significant differences among the samples (p < 0.001). One hundred consumers evaluated 18 attributes using a nine-point hedonic scale, and all attributes demonstrated statistically significant differences across six samples (p < 0.001). The samples from buckwheat and wheat scored the highest in consumer acceptability. The results indicate a strong positive correlation between overall liking and purchase intention, with sensory attributes such as nutty flavor, cohesiveness, appearance, moistness, color, texture, and inner softness positively influencing consumer acceptability. The attributes affecting negatively were thick throat sensation, unique flavor, and stuffiness. This study is expected to provide data to aid in the development of better-tasting gluten-free products that meet customer and market needs.